1995
DOI: 10.1079/bjn19950030
|View full text |Cite
|
Sign up to set email alerts
|

Both raw and retrograded starch decrease serum triacylglycerol concentration and fat accretion in the rat

Abstract: Male Wistar rats were meal-fed on diets containing various amounts of resistant starch in the form of raw starch (either amylomaize starch, potato starch or modi6ed high-amylase starch) or retrograded starch (prepared from each of the starches) for 6 weeks. Two diets containing normal maize starch were fed as diets poor in resistant starch. Energy absorption (energy consumption minus faecal energy loss), growth, weight of the epididymal fat pads, serum total cholesterol and triacylglycerol concentrations and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
46
2
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 23 publications
4
46
2
1
Order By: Relevance
“…In human study, dietary high-amy lose cornstarch compared to low-amylose starch decreased blood cholesterol concentrations by 30-36% (28). The range of cholesterol lowering was from 8% to 23% in subsequent studies (3)(4)(5)(6). Triacylglycerol con centration changes were more variable than cholesterol with the range of 0-42% (3-5).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In human study, dietary high-amy lose cornstarch compared to low-amylose starch decreased blood cholesterol concentrations by 30-36% (28). The range of cholesterol lowering was from 8% to 23% in subsequent studies (3)(4)(5)(6). Triacylglycerol con centration changes were more variable than cholesterol with the range of 0-42% (3-5).…”
Section: Discussionmentioning
confidence: 95%
“…Even though the importance of resistant starch to human health problems such as obesity, diabetes, ath erosclerosis, and cancer has not been clearly elucidated, its hypolipidemic (3-7) and occasional prebiotic effects (8)(9)(10)(11) were noticed. It is generally accepted that RS replaced for digestible starch in the diet can lower serum cholesterol concentrations in normal or hyper cholesterolemic conditions in animals (3)(4)(5)(6)(7). However, tying time, and gut hormone profiles (15)(16)(17).…”
mentioning
confidence: 99%
“…Although the heterogeneous nature of traditional dietary fibre supplements is well documented, it is equally important to recognise that RS varieties originating from different plant sources and manufactured with alternative processing technologies will possess unique physiochemical properties (5) . RS is generally classified into four distinct types: physically entrapped, inaccessible starch; native granular starch; retrograded starch; chemically modified starch (6) .Due to its physiochemical attributes, RS is a particularly useful functional food additive to manage weight loss (7) , improve insulin sensitivity (8) and reduce dyslipidaemia (9) . Furthermore, RS consumption is believed to improve intestinal health and function by increasing micronutrient absorption and favourably altering bacterial fermentation patterns in the large intestine (10,11) .…”
mentioning
confidence: 99%
“…High-amylose corn starch (HACS) contains RS2, ungelatinized starch granules that are highly resistant to digestion by ␣-amylase until gelatinized. Several studies have shown that HACS (RS2) reduces serum cholesterol and triglyceride concentrations in rats (17,30,53) and hamsters (49).CMS are RS4-type resistant starch, which are more resistant to retrogradation, have a higher viscosity, and are more stable in response to acid and high temperature than native starch. Therefore, CMS are increasingly used by the food industry to improve the physical properties of various food items, including baby food.…”
mentioning
confidence: 99%
“…High-amylose corn starch (HACS) contains RS2, ungelatinized starch granules that are highly resistant to digestion by ␣-amylase until gelatinized. Several studies have shown that HACS (RS2) reduces serum cholesterol and triglyceride concentrations in rats (17,30,53) and hamsters (49).…”
mentioning
confidence: 99%